1996
DOI: 10.1164/ajrccm.153.4.8616572
|View full text |Cite
|
Sign up to set email alerts
|

Increased MCP-1, RANTES, and MIP-1alpha in bronchoalveolar lavage fluid of allergic asthmatic patients.

Abstract: Chemokines are cytokines that induce chemotaxis of inflammatory cells. We studied the presence of chemokines in bronchoalveolar lavage fluid (BALF) obtained from nine allergic asthmatic patients and six nonsmoking normal individuals. The cells were pelleted, and ribonucleic acid (RNA) was extracted by using RNAzol B. BALF was assayed for monocyte chemoattractant protein-1 (MCP-1), regulated upon activation in normal T cells, expressed, probably secreted (RANTES), macrophage inflammatory protein-1alpha (MIP-1al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
170
3
2

Year Published

1997
1997
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 285 publications
(179 citation statements)
references
References 0 publications
4
170
3
2
Order By: Relevance
“…Chemokines present an important role in the physiopathology of asthma, such as activation of the inflammatory cascade, bronchial hyperresponsiveness, and airway remodeling (2,22,45,51). In accordance with current literature, our mouse model of allergic lung inflammation presented an increased expression of MCP-1 by inflammatory cells, both in the pulmonary arteries and lung parenchyma (Figs.…”
Section: Discussionsupporting
confidence: 89%
“…Chemokines present an important role in the physiopathology of asthma, such as activation of the inflammatory cascade, bronchial hyperresponsiveness, and airway remodeling (2,22,45,51). In accordance with current literature, our mouse model of allergic lung inflammation presented an increased expression of MCP-1 by inflammatory cells, both in the pulmonary arteries and lung parenchyma (Figs.…”
Section: Discussionsupporting
confidence: 89%
“…This is consistent with data showing that its expression is upregulated in several inflammatory conditions, such as rheumatoid arthritis 17 and multiple sclerosis, 18 as well as asthma. [8][9][10][11] Our data indicated that −403 A is more common in asthmatics, both atopic and non-atopic. This observation is supported by Ying et al 19 who showed that RANTES expression was higher in bronchial mucosa from both types of asthma.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 Furthermore, increased levels of RANTES and other members of the C-C family of chemokines (MIP-1␣, MCP-1) have been detected in the nasal secretions of atopic patients exposed to local allergen challenge 8 and were found in higher levels in the bronchial lavage fluid of patients with active asthma. 9 RANTES has also been found at significantly higher levels in patients during asthma attacks than in those with asymptomatic stages or in controls. 10 In addition, the number of eosinophils recruited to the lung is strongly correlated with the concentration of immunoreactive RANTES.…”
Section: Introductionmentioning
confidence: 95%
“…It has been reported that CCL2 concentration in bronchoalveolar lavage fluid was found to be elevated in allergic asthmatic patients. 37 In addition, CCL2 can initiate leukocyte infiltration and inflammatory responses by inducing chemotaxis of monocytes, T lymphocytes, natural killer cells, eosinophils and basophils, and by degranulation and histamine release from both basophils and mast cells. [38][39][40] Taken together with the evidence demonstrating IL-33 as a chemoattractant for Th2 lymphocytes, 12 the significant CCL2 release from eosinophils upon IL-1b, IL-18 and IL-33 activation may facilitate the locomotion of both eosinophils and other leukocytes to promote the development of allergic inflammation.…”
Section: Il-33 Activates Eosinophilsmentioning
confidence: 99%